Angiotensin receptor-neprilysin inhibitor therapy and recurrence of atrial fibrillation after radiofrequency catheter ablation: A propensity-matched cohort study - Dong, Youzheng; Xiao, Shucai; He, Jinwu; Shi, Kaixin; Chen, Si; Liu, Deping; Huang, Bin; Zhai, Zhenyu; Li, Juxiang (Frontiers in Cardiovascular Medicine, 2022)
Background: Compare to conventional medicines, angiotensin receptor-neprilysin inhibitor (ARNI) could further improve the prognosis for multiple cardiovascular diseases including heart failure, hypertension and myocardial infarction (MI). However, the relationship between ARNI therapy and recurrence of atrial fibrillation (AF) after radiofrequency catheter ablation is currently unknown. Methods: This study is a retrospective cohort study. Consecutive persistent or paroxysmal AF patients undergoing first‐time radiofrequency ablation were enrolled from February 2018 until October 2021. we compared the risk of AF recurrence in patients with catheter ablation who received ARNI with the risk of AF recurrence in those who received angiotensin-converting enzyme inhibitor (ACEI). The propensity-score matched analysis was conducted to examine the effectiveness of ARNI. We used Cox regression model to evaluate AF recurrence events. Results: Among 679 eligible patients, 155 patients with ARNI treatment and 155 patients with ACEI treatment were included in the analyses. At a median follow-up of 228 (196-322) days, ARNI as compared with ACEI, was associated with a lower risk of AF recurrence (adjusted hazard ratio (HR), 0.39; 95% confidence interval [CI], 0.24 to 0.63; P<0.001). In addition, no interaction was found in subgroup analysis. Conclusion: ARNI treatment was associated with a decreased risk of AF recurrence after first‐time radiofrequency catheter ablation.